'Think about what our industry stands for….': exploring the impact of external factors on line manager perceptions of graduate employability. Issue 5 (3rd September 2019) - Mullen, E.; Alexander, J.; Coates, N.
ABSTRACT: Increasing emphasis is being placed upon employer expectations in research on graduate employability, in response to the widely claimed gap between employer expectations and graduates' understanding of these expectations. For graduates, being uncertain of their employer's expectations may threaten the ease of their transition into the workplace and their job satisfaction, even leading to issues around graduate retention for employers. External influences on the graduate labour market such as differences in industry/sector level expectations and economic/political factors, can pose further complications. This paper presents a cross-industry analysis of employer expectations of graduates, drawing from four selected case study vignettes aimed at uncovering insights into these variances. Findings offer implications for policy makers and higher education providers around the design and delivery of a curriculum that appropriately prepares students for the graduate labour market, whilst also catering for industry-level expectations particularly in light of the UK's forthcoming departure from the EU.